A Follow-up Study of Graduates in the Distance Learning System of Master of Nursing Science Program in Community Health Nurse Practitioner, Academic Year 2017 - Jantacumma, Napaphen; Moolsart, Sutteeporn; Iemsawasdikul, Warinee; Nuysri, Mukda; Pinchaleaw, Duangkamol (Journal of The Royal Thai Army Nurses, 2020)
This research aimed to study the desirable characteristics of graduates of Master of Nursing Science Program in Community Health Nurse Practitioner according to the perception of graduates, colleagues and supervisors and to compare the desirable characteristics between graduates colleagues and supervisors’ perception. The sample consisted of 3 groups: 1) 9 graduates, 2) 15 colleagues and 3) 9 supervisors. The tools used for data collection were 2 types: 1) the questionnaire for assessing the six desirable characteristics follow by TQF frameworks which have passed the content validation by 3 experts. The content validity index is 0.91 and the reliability is 0.97. 2) the structural question for in-depth interviews. The result show that the graduates, colleagues, and the supervisors perceived the overall desirable characteristics at the high level ( x̄ = 4.29, SD = 0.67), and the highest level by ( x̄ = 4.58, SD = 0.56) and ( x̄ = 4.58, SD = 0.63) respectively. There are two aspects that all groups perceived the same as the highest level; the outcome of interpersonal relationship skills and responsibilities and the professional practice skills. The result of comparing the desirable characteristics according to the perception of graduates, colleagues and supervisors found that there was only one aspect of knowledge that had different perceptions with statistically significant at .05. The results of the study showed that the aspect of learning skills in communication analysis and information technology was the lowest score ( x̄ = 4.32, SD = 0.55), so the course should encourage learners to improve their analytical, communication and information technology skills to ensure that students are confident and able to use the media to promote the most effective distance learning.